TANGGUNG JAWAB PERUSAHAAN DALAM PELAKSANAAN CSR (CORPORATE SOCIAL RESPONSIBILITY) KEPADA MASYARAKAT OLEH PT. PERKEBUNAN NUSANTARA I LANGSA DI GAMPONG ALUE DUA - Mulyana Mulyana; Ramziati R; Nasrianti N (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2018)
The implementation of corporate responsibility by PT. Perkebunan Nusantara I Langsa ithe form of partnership and community development programs by observing Law Number 40 year 2007 concerning Limited Liability Companies, Government Regulation Numer 47 year 2012 and strengthened by Ministerial Regulation Number PER-02/MBU/7/2017 concerning the Partnership and Community. Which cannot be denied that the positive impact on the community and environment, specifically in terms of granting capital loans as venture capital for fostered partners in Gampong Alue Dua. in the case of granting capital loasn, a legal relationship arises, namely rights and obligations between the company and the fostered partners considers that the venture capital fund is a grant from the campany. The purpose of this study is to find out and explain the implementation of corporate responsibility to the community and the environment, and explain the implementation constraints and efforts to resolve the implementation of corporate responsibility. This research in an empirical juridical legal research, with qualitative legal research types, the source of legal material used is primary and secondary legal materials, research collection techniques are carried ou by interview and literature study methods, research analysis is done by descriptive analysis. Based on the results of research that PT. Perkebunan Nusantara I Langsa has implemented corporate social resposibilty in the from of the Partnership and Community Development Program. The constraints and resolution efforts faced by PT Perkebunan Nusantara I Langsa in the implementation of corporate social responsibility are divided into two, namely in the Partnership Program, the obstacles include: difficulty finding loan data, no confiscation seizure, wrong perception from the community, The Community Development Program has problems, namely difficulties in place surveys, The solution is a persuasive approach. It is recommended to the company in the partnership program the need for a detailed explanation in the nechanism to be followed by the fostered partners from various stages so that the company has no difficulty in billing the fostered partners, and the company can balance petigas with the company’s work area so that it is easy to conduct surveys or the didtribution of aid funds right on target. Key words: Corporate Social Responsibility, PKBL, Implementation.